2021
DOI: 10.1111/trf.16391
|View full text |Cite
|
Sign up to set email alerts
|

Examining knowledge translation in blood donor research: A review of vasovagal reaction literature

Abstract: Background Knowledge translation focuses on the transfer of research findings into policy and practice. To provide insight into the state of knowledge translation in blood donor research, we undertook a rapid review of a key research area in the field with high potential for translation, vasovagal reactions (VVRs). We examined the number and nature of VVR‐related studies to determine the availability of research evidence, and mapped the included articles along the research‐to‐practice trajectory using the Know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This suggests that providing KT training to transfusion medicine researchers may be an effective strategy to increase KT in this area. Whilst this difference may be attributed to researchers with an interest in KT undergoing training, many of our surveyed sample identi ed that they would like to have access to KT education and training (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that providing KT training to transfusion medicine researchers may be an effective strategy to increase KT in this area. Whilst this difference may be attributed to researchers with an interest in KT undergoing training, many of our surveyed sample identi ed that they would like to have access to KT education and training (23).…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected and managed using REDCap electronic data capture tools hosted at The University of Sydney. Participants were recruited through ve main strategies using a combination of direct emails to corresponding authors of published articles in well-known transfusion medicine journals and grant recipients of research relating to transfusion medicine (n = 1645), distribution via an international blood operator network, and public social media posts in May 2022, with details published elsewhere (23). Participants were excluded from participating in the study if they indicated in the screening question that they did not spend any of their working time on research activities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of vasovagal reaction literature showed that KT is in the early stages in this research area, with few studies published on the implementation or evaluation of evidence-based strategies in practice. 11 Failure to translate knowledge gained from research can result in missed opportunities to optimize transfusion medicine policies and practices informed by current evidence. For example, incorporating strategies that have been found to minimize donor risk of vasovagal reactions can increase the number of completed collections, increase the size of the donor panel by preventing donor lapse, reduce donor risk of injury, and reduce costs to the blood collection agency due to preventing product waste, staff time, and efforts to maintain the donor panel.…”
Section: Introductionmentioning
confidence: 99%
“…The field of transfusion medicine does not appear to be immune to this problem. A recent review of vasovagal reaction literature showed that KT is in the early stages in this research area, with few studies published on the implementation or evaluation of evidence‐based strategies in practice 11 . Failure to translate knowledge gained from research can result in missed opportunities to optimize transfusion medicine policies and practices informed by current evidence.…”
Section: Introductionmentioning
confidence: 99%